Genome Sequence of the White Koji Mold Aspergillus kawachii IFO 4308, Used for Brewing the Japanese Distilled Spirit Shochu - Futagami, Taiki (American Society for Microbiology, 2011)
The filamentous fungus Aspergillus kawachii has traditionally been used for brewing the Japanese distilled spirit shochu. A. kawachii characteristically hyperproduces citric acid and a variety of polysaccharide glycoside hydrolases. Here the genome sequence of A. kawachii IFO 4308 was determined and annotated. Analysis of the sequence may provide insight into the properties of this fungus that make it superior for use in shochu production, leading to the further development of A. kawachii for industrial applications.